Impact of the User-Friendliness of BalitaGrow+ on Compliance with Children's Daily Nutrition Column Completing - Pradewi, Ranny Tandria; Marchianti, Ancah C N; Shodikin, Muhammad Ali; Rachmawati, Dwita Aryadina; Kusuma, Irawan Fajar; Sudarmanto, Yohanes (Faculty of Medicine, Universitas Jember, 2024)
Abstract Nutritional imbalances can lead to malnutrition which can affect children's physical and cognitive growth and development. Advances in science and technology have created opportunities for innovation in the form of health applications to help monitor children's growth and development, nutritional status, and children's daily nutritional intake. The factor that influences the intention to use technology is the ease of use. This indicates that the easier the application is to use, the higher a person's interest and compliance will be in using the application regularly. This research aims to determine the effect of ease of use of the BalitaGrow+ application on compliance with filling in the daily nutrition column for children in Rambigundam Village, Jember. This research was an analytical observational research with a cross sectional approach with a sample size of 35 people who meet the criteria. Data analysis used univariate tests and bivariate used the Spearman Rank correlation test. The results obtained from 35 respondents showed that 34 people (97.1%) found it easy to use the BalitaGrow+ application and 31 people (88.6%) had good compliance in filling in the child's daily nutrition column in the application. The results of statistical analysis showed a significance value of p value >0.05 (0.726). So it can be concluded that there was an insignificant influence between the ease of use of the BalitaGrow+ application on compliance with filling in the daily nutrition column for children in Rambigundam Village, Jember. It is suggested to increase the sample size and investigate other influenced factors for future study. Keywords: health application, ease of use, compliance of filling, children’s nutrition